Analisis Skema Rantai Pasok pada Industri Batik Banten - Satyanegara, Diqbal; Hubeis, Musa; Syamsun, Muhammad (Universitas Brawijaya, Indonesia, 2015)
The aims of the research are: (1) to identify the structure of Batik Banten supply chain, (2) to give an alternative scheme of the supply chain of Batik Banten product. Model and concept of Supply Chain Orientation are adopted. Samples are determined by judgment sampling where five experts are participated as respondents. The finding shows the structure of Batik Banten supply chain. The ANP results show Cooperation is the most important factor (0,21159) in order to create the scheme of the supply chain Batik Banten product.